Electrical Potentials of Plant Cell Walls in Response to the Ionic Environment - Shomer, Ilan (The American Society for Plant Biologists, 2003)
Electrical potentials in cell walls (ψ(Wall)) and at plasma membrane surfaces (ψ(PM)) are determinants of ion activities in these phases. The ψ(PM) plays a demonstrated role in ion uptake and intoxication, but a comprehensive electrostatic theory of plant-ion interactions will require further understanding of ψ(Wall). ψ(Wall) from potato (Solanum tuberosum) tubers and wheat (Triticum aestivum) roots was monitored in response to ionic changes by placing glass microelectrodes against cell surfaces. Cations reduced the negativity of ψ(Wall) with effectiveness in the order Al(3+) > La(3+) > H(+) > Cu(2+) > Ni(2+) > Ca(2+) > Co(2+) > Cd(2+) > Mg(2+) > Zn(2+) > hexamethonium(2+) > Rb(+) > K(+) > Cs(+) > Na(+). This order resembles substantially the order of plant-root intoxicating effectiveness and indicates a role for both ion charge and size. Our measurements were combined with the few published measurements of ψ(Wall), and all were considered in terms of a model composed of Donnan theory and ion binding. Measured and model-computed values for ψ(Wall) were in close agreement, usually, and we consider ψ(Wall) to be at least proportional to the actual Donnan potentials. ψ(Wall) and ψ(PM) display similar trends in their responses to ionic solutes, but ions appear to bind more strongly to plasma membrane sites than to readily accessible cell wall sites. ψ(Wall) is involved in swelling and extension capabilities of the cell wall lattice and thus may play a role in pectin bonding, texture, and intercellular adhesion.